White Matter Diffusion Changes during the First Year of Natalizumab Treatment in Relapsing-Remitting Multiple Sclerosis - Wiebenga, O.T.; Schoonheim, M.M.; Hulst, H.E.; Nagtegaal, G.J.A.; Strijbis, E.M.M.; Steenwijk, M.D.; Polman, C.H.; Pouwels, P.J.W.; Barkhof, F.; Geurts, J.J.G. (American Journal of Neuroradiology, 2016)
BACKGROUND AND PURPOSE: Natalizumab treatment strongly affects relapsing-remitting multiple sclerosis, possibly by restraining white matter damage. This study investigated changes in white matter diffusivity in patients with relapsing-remitting multiple sclerosis during their first year of natalizumab treatment by using diffusion tensor imaging.MATERIALS AND METHODS: The study included patients with relapsing-remitting multiple sclerosis initiating natalizumab at baseline (n = 22), patients with relapsing-remitting multiple sclerosis continuing interferon-β or glatiramer acetate (n = 17), and healthy controls (n = 12). Diffusion tensor imaging parameters were analyzed at baseline and month 12. We measured the extent and severity of white matter damage with diffusion tensor imaging parameters such as fractional anisotropy, comparing the patient groups with healthy controls at both time points.RESULTS: The extent and severity of white matter damage were reduced significantly in the natalizumab group with time (fractional anisotropy–based extent, 56.8% to 47.2%; severity, z = −0.67 to −0.59; P = .02); this reduction was not observed in the interferon-β/glatiramer acetate group (extent, 41.4% to 39.1%, and severity, z = −0.64 to −0.67; P = .94). Cognitive performance did not change with time in the patient groups but did correlate with the severity of damage (r = 0.53, P = < .001).CONCLUSIONS: In patients with relapsing-remitting multiple sclerosis starting natalizumab treatment, the extent and severity of white matter damage were reduced significantly in the first year of treatment. These findings may aid in explaining the large observed clinical effect of natalizumab in relapsing-remitting multiple sclerosis.ADaxial diffusivityEDSSExpanded Disability Status ScaleFAfractional anisotropyGAglatiramer acetateIFNbinterferon βNBVnormalized whole-brain volumeMDmean diffusivityRCIReliable Change IndexRDradial diffusivityRRMSrelapsing-remitting multiple sclerosis